Analisis Implementasi Nilai-Nilai Pancasila di Era Globalisasi pada Siswa Kelas V SDN X - Amelia Kirana; Dodik Kariadi; Insan Suwanto (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the implementation of Pancasila values ​​in the era of globalization among fifth-grade students of Singkawang 08 Public Elementary School. Globalization has a significant impact on daily life, both in social, cultural, and educational aspects, so it is important to instill Pancasila values ​​from an early age. This study uses a qualitative approach with a phenomenological design. The research subjects included the principal, class teachers, and fifth-grade students, while data collection techniques were conducted through observation, in-depth interviews, and documentation. Data analysis was carried out through the steps of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of Pancasila values ​​in schools has been carried out consistently through various habituation programs and structured activities. The value of God is realized by getting students used to praying before and after learning activities, participating in religious education, and holding interfaith activities to foster tolerance. The value of humanity is reflected through mutual respect, community service activities, and empathy training in the school environment. The value of unity is fostered through cross-class cooperation, appreciation of diverse cultures, flag ceremonies, and celebrations of national holidays. The values ​​of democracy are implemented through class discussions and student participation in school organizations. The values ​​of social justice are realized through mutual cooperation activities, fundraising, and caring for others. Thus, this study confirms that elementary education plays a crucial role in instilling Pancasila values ​​as preparation for facing the challenges of globalization. The findings highlight that character education based on Pancasila values ​​is essential to preparing young generations to live harmoniously in a global society.